The impact of marketing promotion mix tools and channel of distribution on zakat collection performance: a case study on Pusat Pungutan Zakat- Majlis Agama Islam Wilayah Persekutuan ( PPZ-MAIWP) / Nurul Azian Mamod - Mamod, Nurul Azian (2011)
The research on the impact of marketing promotion mix (tools) and channel of distribution on zakat collection performance was conducted with four objectives which are first to find out the promotional mix tools used by PPZ-MAIWP in enhancing the zakat collection performance, second to determine the channel of distribution of service provided in collecting zakat payment, third to identify the impact of promotional mix tools and channel of distribution of services on zakat collection and fourth to provide recommendation to improve in getting more zakat collection.. The efficient and effective promotion mix tools and distribution channel give advantage to collector and the payee of zakat. Promotion mix tools help PPZ-MAIWP to increase the awareness among people to pay zakat and the distribution channel make the people easy to pay zakat. With the strategy help PPZ-MAIWP to achieve their objective. The research paper also further identified the impact of the promotion mix tools and the distribution channel to zakat collection performance. For example, the drastic increase in total collection had shown the important of this marketing strategy. Some recommendations are made to enable PPZ to use more of the promotional mix tools. So that, collection of zakat can be increased further and the payers of zakat have better understanding towards obligation to pay zakat and how payment can be made more conveniently.